Fragmented livelihoods: a reflection on why few peasants living in poverty join an organization in Niassa (Mozambique). - Johansson,Kajsa (2022)
Abstract his article examines the reasons why peasants living in poverty are unlikely to form or join an organization defending their rights and interests. The study is based on ethnographically inspired fieldwork in the Niassa province, northern Mozambique, and takes peasants’ accounts of their livelihoods as the point of departure. The livelihood analysis is placed within a historical and structural process. The article suggests that four dimensions of fragmentation of peasants’ livelihoods hamper the conditions for collective organizations. Firstly, every peasant household is, at any given point in time, engaged in a number of different livelihood activities to ensure its production and reproduction. Secondly, the composition of these activities varies between households. Thirdly, the activities are constantly changing. Fourthly, there is socio-economic differentiation among peasant households. These four dimensions make it difficult to identify central and enduring interests and conflicts peasants are engaged in that could be the foundation for their collective organization.